Inner Experiences: Theory, Measurement, Frequency, Content, and Functions - Alain Morin (Frontiers Research Topics, 2016)
One fundamental topic of scientific inquiry in psychology is the study of what William James called the 'stream of consciousness', our ongoing experience of the world and ourselves from within-our inner experiences. These internal states (aka "stimulus-independent thoughts") include inner speech, mental imagery, feelings, sensory awareness, internally produced sounds or music, unsymbolized thinking, and mentalizing (thinking about others' mental states). They may occur automatically during mind-wandering (daydreaming) and resting-state episodes, and may focus on one's past, present, or future ("mental time travel" - e.g., autonoetic consciousness). Inner experiences also may take the form of intrusive or ruminative thoughts. The types, characteristics, frequency, content, and functions of inner experiences have been studied using a variety of traditional methods, among which questionnaires, thought listing procedures (i.e., open-ended self-reports), thinking aloud techniques, and daily dairies. Another approach, articulatory suppression, consists in blocking participants' use of verbal thinking while completing a given task; deficits indicate that inner speech plays a causal role in normal task completion. Various thought sampling approaches have also been developed in an effort to gather more ecologically valid data. Previous thought sampling studies have relied on beepers that signal participants to report aspects of their inner experiences at random intervals. More recent studies are exploiting smartphone technology to easily and reliably probe randomly occurring inner experiences in large samples of participants. These various measures have allowed researchers to learn some fundamental facts about inner experiences. To illustrate, it is becoming increasingly clear that prospection (future-oriented thinking) greatly depends on access to autobiographical memory (past-oriented thinking), where recollection of past scenes is used as a template to formulate plausible future scenarios. The main goal of the present Research Topic was to offer a scientific platform for the dissemination of current high-quality research pertaining to inner experiences. Although data on all forms of inner experiences were welcome, reports on recent advances in inner speech research were particularly encouraged. Here are some examples of topics of interest: (1) description and validation of new scales, inventories, questionnaires measuring any form of inner experience; (2) novel uses or improvements of existing measures of inner experiences; (3) development of new smartphone technology facilitating or broadening the use of cell phones to sample inner experiences; (4) frequency, content, and functions of various inner experience; (5) correlations between personality or cognitive variables and any aspects of inner experiences; (6) philosophical or theoretical considerations pertaining to inner experiences; and (7) inner experience changes with age.